Factors Affecting the Choice of Irrigation Systems for Florida Tomato Production - Jenna Rogers; Tatiana Borisova; Jeffrey Ullman; Kelly Morgan; Lincoln Zotarelli; Kelly Grogan (EDIS)
Several economic factors should be considered in selecting an agricultural irrigation system. This 7-page fact sheet compares two widely used irrigation systems for tomato production: seepage and sub-surface drip irrigation. Written by Jenna Rogers, Tatiana Borisova, Jeffrey Ullman, Kelly Morgan, Lincoln Zotarelli, and Kelly Grogan, and published by the UF Department of Food and Resource Economics, October 2014. (UF/IFAS Photo: Tyler Jones)